Legal Ethics and Professional Responsibility in a Global Context - Julian Lonbay (Washington University Global Studies Law Review, 2005)
Where did two world wars start in the twentieth century? The cure was to have an increasing number of structural links at the economic, political, and importantly for us, legal dimensions between European nations. The nation-State in Europe is giving way to a complex system of multi-level governance. These remarks point out the implications for lawyers and legal practice in Europe, in particular when it comes to deontological rules that govern professional legal life. This paper provides a quick introduction on how the free movement of lawyers across European borders came about. Certainly, there have been ethical clashes and clashes of ethical codes that have not been satisfactorily dealt with. The main issuesthis essay focuses on are competence and bar admission—because some of the mobility rights allow dual or even triple qualification.
Keywords: Legal ethics; European Union